(untitled) (Proceedings of International Educators Conference, 2024)
This article is devoted to the socio-psychological foundations of professional reflex in the employees of the prosecutor’s office system and provides for the study of such as professional, scientific, psychological training of the employees of the prosecutor’s office system. Also, in the content of the article, the individual psychological characteristics of the employees of the prosecutor’s office system, the socio-psychological image of the individual and the socio-psychological study of the formation of professional reflex are widely covered.